Circuit Eraser: A Tool for Iterative Design with Conductive Ink - Narumi, Koya; Shi, Xinyang; Hodges, Steve; Kawahara, Yoshihiro; Shimizu, Shinya; Asami, Tohru (CHI 2015 Extended Abstracts, 2015)
Recent advances in materials science have resulted in a range of commercially viable and easy-to-use conductive inks which many practitioners are now using for the rapid design and realization of interactive circuits. Despite the ease with which hobbyists, educators and researchers can construct working circuits, a major limitation of prototyping with conductive ink is the difficulty of altering a design which has already been printed, and in particular removing areas of ink. In this paper we present Circuit Eraser, a simple yet effective tool which enables users to ‘delete’ existing conductive patterns. Through experimentation we have found an effective combination of materials which result in the removal of only the thin surface layer composed of ink particles, with minimal damage to the surface coating of the paper. This important characteristic ensures it is possible to re-apply conductive ink as part of an on-going design iteration. In addition to a lab-based evaluation of our Circuit Eraser which we present here, we have also used our technique in several practical applications and we illustrate one of these, namely the iterative design of a radio-frequency antenna.